HUGE PANCREATIC CALCIFICATIONS-----AN UNUSUAL CASE OF PANCREATIC DIVISUM - Muhammad Tariq; Zaheer Mustafa (Journal of University Medical & Dental College, 2014)
ABSTRACT: The pancreas is located in the midline of the back of the abdomen, closely associated with the liver, stomach, and duodenum. The pancreas is an unusual gland because it has both endocrine and exocrine functions. There are various types of congenital anomalies of the pancreas in humans. These include Anomalous pancreaticobiliary junction (APBJ) , Choledochal cysts, Annular pancreas and pancreas divisum. Pancreas divisum is a congenital anomaly in which ventral and dorsal pancreatic ducts do not fuse together. The presence of pancreatic calcifications signifies the pancreatic disease. Today, our ability to image the pancreas has greatly advanced with modalities including sonography, CT, endoscopic retrograde cholangiopancreatography, and MR imaging. This improved visualization of the pancreas allows better identification of pancreatic calcifications and their underlying cause. Common causes of pancreatic calcifications include inflammatory such as chronic alcoholic pancreatitis, developmental such as hereditary pancreatitis, cystic fibrosis, pancreas divisum and annular pancreas, neoplastic such as ductal adenocarcinoma and idiopathic such as in older patients. We present a case of 45-year-old male patient presented with epigastric pain off and on for the last one year. His ultrasonography showed a large calcification in the region of pancreas. Pancreas was not separately visualized. CT scan of abdomen also revealed two large calcifications within the pancreas. His MRCP demonstrate pancreas divisum with heavy calcifications in pancreatic parenchyma.